Writing a Curriculum Vitae on a Digital Platform, Canva - Puji Lestari; Lambok Hermanto Sihombing (Universitas Riau, 2022)
Most of Vocational High School students are designed to work after they graduate. They are shaped to be the professional workers in a company so that they have to master various skills. One of the basic competencies they need to master is writing. Writing skill can help them prepare the application letter when they apply for the job. Thus, this study aims to analyze the students’ creativity in writing a Curriculum Vitae using a digital platform namely Canva. The object of this research was the students of Binakarya Mandiri Vocational High School Bekasi, grade XII majoring Technical Engineering. There were 30 students in the class. However, the researchers took 3 students’ digital creative results as the samples of this research. Through a qualitative approach, the researchers applied the Teaching Principle theory by H. Douglas Brown and Heekyong Lee and the concept of Media Education from Alexander Fedorov. The result shows that the students in grade XII majoring Technical Engineering are more well-prepared and creative in writing the Curriculum Vitae using Canva.